STUDI PENGEMBANGAN MODEL EKONOMI MAKRO DAN KEBIJAKAN EKONOMI REGIONAL KOTA PAGAR ALAM - Fachrizal Bachri (Department of Development Economics, Universitas Sriwijaya, 2007)
Study of macroeconomic model is the starting process of development planning. It is used to find the development stage for future development planning and regional economic policy in Kota Pagar Alam city. The objective of this study is to find basic information for sectoral development planning including the sectoral. The next, it is used to choose macroeconomic policy scenario and also to point out the growth point in Kota Pagar Alam which is based on the regional condition.Qualitative and quantitative descriptive analyses are used as analyses method. Qualitative descriptive analyses is used to calculate economic growth, sectoral contribution percentage, population growth, unemployment rate, dependency ratio, employment participation rate and scalogram. While quantitative descriptive analyses is used to calculate employment elasticity, Incremental Output Ratio (ICOR), Location Quotient (LQ) and Shift Share. The study results show that there are three regional growth points as follows: First, Pagar Alam Utara subdistrict regional growth point as the center of trade acivity, farming, warehouses, banking, tourism and industrial estate. Supporting region is Dempo Utara subdistrict . Second, Pagar Alam Selatan subdistrict regional growth point as the center of fishery production, small scale industry, trade, warehouses, banking and livestock. Supporting region is Dempo Utara subdistrict. The third, this is a newly alternative regional growth point which is based on the potential condition and geographical location of Pagar Alam city. The growth point is located in Dempo Selatan subdistrict. It will be used as the center of food crops paddy and secondary food crops, estate crop coffee, livestock, mining and quarrying C type. The upporting region will be Dempo Tengah subdistrict . Keywords: development planning, regional policy